Jesus Narrativo: oralidade cristã entre história, memória e mítica / Narrated Jesus: Christian orality between history, memory and myth - Alonso, Leandro Seawright (PLURA, Revista de Estudos de Religião / PLURA, Journal for the Study of Religion, 2012)
<span style="font-size: 10.0pt; line-height: 115%; font-family: ";Bookman Old Style";,";serif";; mso-fareast-font-family: Calibri; mso-bidi-font-family: ";Times New Roman";; mso-ansi-language: PT-BR; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Consideramos as diferentes reflexões acadêmicas convencionais sobre o Jesus Histórico, o Jesus da Fé e, como alternativa, um novo conceito emergente de Jesus Narrativo. Se é verdade que Jesus de Nazaré morreu na grande história, então também é verdade que reviveu na memória coletiva dos cristãos. Abstract <span style="font-size: 10.0pt; line-height: 115%; font-family: ";Bookman Old Style";,";serif";; mso-fareast-font-family: Calibri; mso-bidi-font-family: ";Times New Roman";; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">We consider the different conventional academic reflections on historical Jesus, the Jesus of Faith, and alternatively a new emerging concept of the Narrated Jesus. If it is true that Jesus of Nazareth died in the great history, then it is true that he revived within the collective memory of the Christians.